Cost‐effectiveness of motivational intervention with significant others for patients with alcohol misuse. (8th January 2016) - Shepard, Donald S.; Lwin, Aung K.; Barnett, Nancy P.; Mastroleo, Nadine; Colby, Suzanne M.; Gwaltney, Chad; Monti, Peter M.
Abstract: Aims: To estimate the incremental cost, cost‐effectiveness and benefit–cost ratio of incorporating a significant other (SO) into motivational intervention for alcohol misuse. Design: We obtained economic data from the one year with the intervention in full operation for patients in a recent randomized trial. Setting: The underlying trial took place at a major urban hospital in the United States. Participants: The trial randomized 406 (68.7% male) eligible hazardous drinkers (196 during the economic study) admitted to the emergency department or trauma unit. Intervention: The motivational interview condition consisted of one in‐person session featuring personalized normative feedback. The significant other motivational interview condition comprised one joint session with the participant and SO in which the SO's perspective and support were elicited. Measurements: We ascertained activities across 445 representative time segments through work sampling (including staff idle time), calculated the incremental cost in per patient of incorporating an SO, expressed the results in 2014 US, incorporated quality and mortality effects from a closely related trial and derived the cost per quality‐adjusted life‐year (QALY) gained. Findings: From a health system perspective, the incremental cost per patient of adding an SO was 341.09 [95% confidence interval (CI) = 244.44–437.74]. The incremental cost per year per hazardous drinker averted was 3623 (CI = 1777–22 709), the cost per QALY gained 32 200 (CI = 15 800–201 700), and the benefit–cost ratio was 4.73 (95% CI = 0.7–9.66). If adding an SO into the intervention strategy were concentrated during the hours with highest risk or in a trauma unit, it would become even more cost‐beneficial. Conclusions: Using criteria established by the World Health Organization (cost‐effectiveness below the country's gross domestic product per capita), incorporating a significant other into a patient's motivational intervention for alcohol misuse is highly cost‐effective.